Síntese e atividades anti-ureolítica e antiproliferativa de benzimidazois e benzotiazois - Débora Pereira Araújo (2015)
Benzimidazoles and benzothiazoles comprise two classes of heterocyclic compounds that bear a benzene ring fused to an imidazole and thiazole ring, respectively. These cores are privileged scaffold as attested by their use for the development of products of agricultural, pharmaceutical and technological interests. The first chapterof this work describes the sodium bisulfide-catalyzed synthesis of 24 benzimidazoles and 19 benzothiazoles under micro-wave irradiation and solvent-free condition. Reaction yields ranged from 80% to 100% regardless of the compound class. Mass Spectrometry studies allowed for understanding the mechanism of reaction by which benzimidazoles are formed. An adduct between the aldehyde and sodium bisulfide is initially formed followed by its reaction with an ortho-phenylenediamine to furnish the corresponding monoimine. The monoimine undergoes cyclization and oxidation to provide the corresponding benzimidazole. Differently from the previous reports, the alleged oxidant agent sulfur dioxide (SO2) was not detected in the reaction medium. The second chapter describes the effect of synthesized benzimidazoles and benzothiazoles on the ureolytic activity of Canavalia ensiformis and soil ureases. Twenty benzimidazoles and 7 benzothiazoles inhibited C. ensiformis urease by at least 5%; the benzimidazoles 15and 17and benzothiazoles 37and 38were found the most active as attested by the percentage of enzyme inhibition higher than 25%. The benzimidazole 17and benzothiazole 37exhibited mechanism of action typical of mixed inhibitors, demonstrating that such compounds are able to bind to both the active site and the urea-urease complex. The inhibition profile for benzimidazoles and benzothiazoles on soil ureases was quite distinct from that ofC. ensiformisurease type III. A total of 11 benzimidazoles and 9 benzothiazoles inhibited soil ureases by at least 20%. Some of them were as potent of more potent than N-(butyl)thiphosphoric triamide (NBPT; 35% inhibition), a urease inhibitor used as additive in urea-based fertilizers. Chapter 3 deals with the inhibitory effect of synthesized benzimidazoles and benzothiazoles on the growth of 9 cancer cell lines. A human keratinocyte nontumorogenic cell line (HaCat) was used for investigating the tested compounds selectivity. All synthesized compounds were effective against the studied cancer cells in a concentration-dependent fashion. The compound 16 was determined to be the most potent benzimidazole against all cancer cell lines while the benzothiazoles 36 and 40were the most potent on kidney cancer cells (786-0 line). Notably, both benzimidazoles and benzothiazoles were less toxic to non-tumorogenic cells (HaCat line) when compared to doxorubicin, a reference drug. Overall,benzimidazoles and benzothiazoles have been demonstrated to be lead compounds for the design of novel additives for urea-based formulations and anticancer agents.